Gestational and lactational NSAID exposure induces long-term reproductive and behavioral alterations in male rats - Magalhães, Luara [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used for pain, fever, and inflammation, with frequent administration even among pregnant and lactating women. Since NSAIDs readily cross the maternal-fetal interface and inhibit Cyclooxygenase (COX1 and COX-2) enzymes, they significantly reduce prostaglandin E2 (PGE2) synthesis. PGE2 plays a crucial role in nervous system development, particularly in brain sexual differentiation process vulnerable to endocrine disruptors. Therefore, NSAID use during pregnancy raises major developmental concerns. This study evaluated the effects of gestational and lactational exposure to NSAIDs on sexual behavior and fertility in adult male rat offspring. Pregnant rats were randomized into four groups for daily oral treatment (gavage) from gestational day (GD) 15 to postnatal day (PND) 22, a critical period for male brain sexual differentiation: 1. Control (alcohol 7.5% 1mL/kg); 2. Paracetamol (125 mg/kg); 3. Acetylsalicylic acid (ASA, 6 mg/kg); and 4. Nimesulide (11 mg/kg). Doses were based on human therapeutic equivalents adjusted for body surface area. Male offspring were assessed for sexual and play behavior, fertility, sperm, and hematological parameters. Paracetamol exposure reduced testicular sperm count and daily sperm production and increased cytoplasmic droplets, indicating impaired spermiogenesis. It also elevated the frequency of female-typical sexual behavior, suggesting incomplete brain defeminization. ASA exposure led to a higher incidence of sperm abnormalities and reduced social play, indicative of androgenic disruption. Nimesulide exposure produced no significant changes, though it tended to increase prostate weight and post-implantation losses. These findings demonstrate that developmental exposure to NSAIDs interferes with brain sexual differentiation, resulting in persistent alterations in male reproductive function and behavior.
Exposição a AINEs durante a gestação e lactação induz alterações reprodutivas e comportamentais de longo prazo em ratos machos
Keywords: Acetaminophen; Acetylsalicylic Acid; Nimesulide; NSAIDs; Brain sexual differentiation; Aspirina; Agentes anti-inflamatórios não esteróides